Quantum Reading As An Instructional Innovation For Literacy Development In Islamic Educational Perspective - Syauqy Sabila Rosyad; Moh. Sutomo; Mu'alimin (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2026)
This study examines the implementation of the Quantum Reading method as an instructional innovation for improving reading comprehension among fifth-grade students at SDN Karangduren 01 Balung Jember, Indonesia. The research was motivated by students' low reading literacy, limited ability to identify main ideas, weak reading fluency, and the dominance of teacher-centered reading instruction. Using an explanatory mixed-methods design with a one-group pretest-posttest model supported by qualitative inquiry, this study involved 19 fifth-grade students, one classroom teacher, and the school principal. Quantitative data were obtained through a reading comprehension test, while qualitative data were collected through classroom observation, interviews, and documentation. The intervention was conducted in four meetings using seven stages of Quantum Reading: recognition, assimilation, intra-integration, extra-integration, storage, recall, and communication. The findings indicate a substantial improvement in students' reading outcomes: the mean score increased from 66.84 to 86.32, learning mastery rose from 36.84% to 94.74%, and the normalized gain reached 0.59, which falls into the moderate category. Qualitative findings show that students became more motivated, confident, focused, and able to connect reading texts with their daily experiences. From an Islamic educational perspective, Quantum Reading is pedagogically relevant because it supports meaningful learning, active engagement with knowledge, the cultivation of learning adab, and the holistic development of students' cognitive, affective, social, and spiritual potential. This study contributes to literacy learning by demonstrating that reading instruction can be improved through joyful, multisensory, contextual, and value-oriented classroom practices in elementary education.